1997
DOI: 10.1148/radiology.202.3.9051019
|View full text |Cite
|
Sign up to set email alerts
|

Detection of extracapsular extension of prostate carcinoma with endorectal and phased-array coil MR imaging: multivariate feature analysis.

Abstract: Obliteration of the rectoprostatic angle and asymmetry of the neurovascular bundle were most indicative of extracapsular extension. Reader experience plays an important role in the ability to interpret prostate MR images and is an important contributor to interobserver variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0
16

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(151 citation statements)
references
References 0 publications
2
133
0
16
Order By: Relevance
“…It was found that tumor volume per lobe estimated by MRSI was significantly (P Ͻ 0.01) higher in patients with ECE (2.14 Ϯ 2.3 cm 3 ) than in patients without ECE (0.98 Ϯ 1.1 cm 3 ) (29). Moreover the addition of an MRSI estimate of tumor volume to high-specificity MRI findings for ECE (74) improved the diagnostic accuracy and decreased the inter-observer variability of MRI in the diagnosis of extracapsular extension of prostate cancer (Fig. 2) (29).…”
Section: Improved Prostate Cancer Staging Using Combined Mri/mrsimentioning
confidence: 94%
See 1 more Smart Citation
“…It was found that tumor volume per lobe estimated by MRSI was significantly (P Ͻ 0.01) higher in patients with ECE (2.14 Ϯ 2.3 cm 3 ) than in patients without ECE (0.98 Ϯ 1.1 cm 3 ) (29). Moreover the addition of an MRSI estimate of tumor volume to high-specificity MRI findings for ECE (74) improved the diagnostic accuracy and decreased the inter-observer variability of MRI in the diagnosis of extracapsular extension of prostate cancer (Fig. 2) (29).…”
Section: Improved Prostate Cancer Staging Using Combined Mri/mrsimentioning
confidence: 94%
“…However, the assessment of cancer spread through the prostatic capsule is more difficult (81% accuracy) (26) and is becoming even harder to assess as fewer men demonstrate gross cancer spread (directly visible on MRI) due to earlier cancer detection. In a recent study of 53 patients with earlystage prostate cancer, tumor volume estimates based on MRSI findings were combined with high-specificity MRI criteria (74) in order to assess the ability of combined MRI/MRSI to predict extracapsular cancer spread. This study was based on prior histopathologic studies that demonstrated that tumor volume was a significant predictor of extracapsular extension (ECE) of prostate cancer (75,76).…”
Section: Improved Prostate Cancer Staging Using Combined Mri/mrsimentioning
confidence: 99%
“…Subtle signs of EPE used in standardised reporting systems include: extent of contact of the tumour with the capsule, loss of the recto-prostatic angle, bulging or irregularity of the 'pseudo-capsule' , reduced signal in the peri-prostatic fat and asymmetry of the neurovascular bundle; these signs can increase the accuracy of MRI in detecting EPE to 77%-80% [110,111]. The main limitation of MRI in T-staging is limited sensitivity, due to its inability to detect microscopic EPE.…”
Section: Mri In T-staging Treatment Selection and Planningmentioning
confidence: 99%
“…The reasons for this are likely multifactorial: patient selection, different protocols, differences in criteria used for interpretation and subspecialty experience of the radiologist. 6 Yu et al 30 in a study of 77 patients who had stage pT2 (the tumor is confined within the prostate gland) or pT3 (the tumor has extended through the prostatic capsule and/or to the seminal vesicles, but no other organs are affected) PCa and whose MR images were retrospectively reviewed by three readers with varying experience in interpretation of endorectal coil images of the prostate gland showed that reader's experience have an important role. The reader with the most experience achieved the best results for sensitivity, specificity and accuracy, and the interpretations showed a statistically significantly greater area under the receiver operating characteristic curve than those of the less experienced readers.…”
mentioning
confidence: 99%